The Influence of Role Play Engineering And Therapy Cinema to Believe in Self-Class VIII Students in SMP Negeri 4 Pasarwajo - Tarno Tarno; Husniah Husniah; Kapraja Sangadji (Peneliti.net, 2020)
The study aims to determine the effect of Role Playing Techniques and Cinema Therapy on the Self-Confidence of Grade VIII students at SMP Negeri 4 Pasarwajo, as well as describing students' metacognitive awareness based on student grade levels and school origin. Research is a quantitative descriptive study. Data collection techniques using the MAI questionnaire and learning management strategy questionnaire. The results of the analysis of the data that have been done, showed that there was an increase in the confidence of students of class VIII of SMP Negeri 4 Pasarwajo after being given treatments using role playing techniques and Cinema Therapy. From the results of testing the hypothesis of the experimental group in this case using the role playing technique, the value of thitung is 3.56. Medium from distribution list t aims to develop the potential of students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. at 5% significance level, t0,975 (28) = 2,05 was obtained. So it can be concluded that the role playing technique provides an influence or can increase student confidence.